Liminal states: Propertied citizenship and gendered kin work in middle-class Kolkata families. (December 2022) - Donner, Henrike
This article traces the way the intersection between gender, class and family values is reorganised in relation to state policies that enable propertied citizenship through home-ownership. Focusing on ethnographic data from Kolkata, India, it discusses how women realise propertied citizenship in exchange for care work rather than through employment as developmentalist and liberal feminist discourses suggest. Here the way women's lives are envisaged and represented through investment in high levels of educational attainment is in contrast to low levels of employment, symptomatic of what I call 'liminal states' – a gendered state of immaturity and dependence on kin. Home-ownership as a means of 'empowerment' configures the home as the economic and affective focus of gendered care work, which reproduces Berlant's 'cruel optimism', whereby the desire to own a home and the practices of homemaking hamper autonomy and restrict the efficacy of agency.